2017
DOI: 10.3389/fnagi.2017.00318
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Increases Parietal Lobe Cerebral Blood Flow in Chronic Stroke: An Observational Study

Abstract: Exercise is increasingly recommended as an essential component of stroke rehabilitation, yet uncertainty remains with respect to its direct effect on the cerebral vasculature. The current study first demonstrated the repeatability of pseudo-continuous arterial spin labeling (ASL) magnetic resonance imaging (MRI) in older adults with stroke, and then investigated the change in cerebrovascular function following a 6-month cardiovascular rehabilitation program. In the repeatability study, 12 participants at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Sensory impulse is repeatedly introduced into the central nervous system, which plays an essential role in axon sprouting of neurons, transmission of latent pathways, and synapses. Therefore, ultraearly rehabilitation increases the CBF in the penumbra area and revitalizes a part of the neuron [ 27 ]. A study using a rat model of cerebral infarction indicated physical activities within 14 days of onset reduced dendritic branching and prevented the aggravation of nerve conduction [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory impulse is repeatedly introduced into the central nervous system, which plays an essential role in axon sprouting of neurons, transmission of latent pathways, and synapses. Therefore, ultraearly rehabilitation increases the CBF in the penumbra area and revitalizes a part of the neuron [ 27 ]. A study using a rat model of cerebral infarction indicated physical activities within 14 days of onset reduced dendritic branching and prevented the aggravation of nerve conduction [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, running activities post-MCAO in mice increase hippocampal neurogenesis and improve behavioral test scores, elevating functional outcomes in post-stroke recovery (Woitke et al 2017). Altogether, physical activity’s positive effect in stroke is well documented in preclinical studies (Zhang et al 2013; Pan et al 2017; Stradecki-Cohan et al 2017), as well as in clinical trials and meta-reviews (Belfiore et al 2018; Oberlin et al 2017; Robertson et al 2017), and continues to be recommended (Billinger et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although it remains plausible that a longer-term (i.e., Ն6 mo) aerobic training program may be needed to elicit changes in cerebrovascular function such as is documented in stroke survivors (25,40), whether this is similar in COPD still needs to be determined.…”
Section: H388mentioning
confidence: 99%
“…In healthy older adults, 12 wk of progressive aerobic exercise training resulted in significant increases in both CBF velocity and cerebrovascular reactivity to hypercapnia (33). Furthermore, in stroke survivors, 6 mo of exercise training improved cerebrovascular reactivity (25) and increased regional CBF (40). Although the clinical benefits of improving cerebrovascular function specifically in patients with COPD is not known, any improvement in cerebral perfusion and thus O 2 delivery in high-risk clinical populations like those with COPD has the potential to reduce future risk of cognitive decline.…”
Section: Introductionmentioning
confidence: 97%